Brain Derived Neurotrophic Factor and Glial Cell Line-Derived Neurotrophic Factor-Transfected Bone Mesenchymal Stem Cells for the Repair of Periphery Nerve Injury - Zhang, Qiang; Wu, Ping; Chen, Feixiang; Zhao, Yanan; Li, Yinping; He, Xiaohua; Huselstein, Céline; Ye, Qifa; Tong, Zan; Chen, Yun (Frontiers in Bioengineering and Biotechnology, 2020)
Peripheral nerve injury is a common clinical neurological disease. In our previous study, highly oriented poly (L-lactic acid) (PLLA)/soy protein isolate (SPI) nanofiber nerve conduits were constructed and exhibited a certain repair capacity for peripheral nerve injury. In order to further improve their nerve repairing efficiency, the bone marrow mesenchymal stem cells (BMSCs) overexpressing brain derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) were introduced into the conduits as seed cells and then were used to repair the 10-mm sciatic nerve defects in rats. The nerve repair efficiency of the functional nerve conduits was evaluated by gait experiment, electrophysiological test, and a series of assays such as hemotoxylin-eosin (HE) staining, immunofluorescence staining, toluidine blue (TB) staining, transmission electron microscopy (TEM) observation of regenerated nerve and Masson's trichrome staining of gastrocnemius muscle. The results showed that the conduits containing BMSCs overexpressing BDNF and GDNF double-factors group had better nerve repairing efficiency than blank BMSCs and single BDNF or GDNF factor groups, and superior to autografts group in some aspects. These data demonstrated that BDNF and GDNF produced by BMSCs could synergistically promote peripheral nerve repair. This study shed a new light on the conduits and stem cells-based peripheral nerve repair.